Microencapsulation of Theobroma cacao L polyphenols: A high-value approach with in vitro anti-Trypanosoma cruzi, immunomodulatory and antioxidant activities (2024)
Chagas disease (CHD) is the highest economic burden parasitosis worldwide and the most important cardiac infection, without therapeutic alternatives to halt or reverse its progression. In CHD-experimental models, antioxidant and anti-inflammatory compounds have demonstrated therapeutic potential in cardiac dysfunction. Theobroma cacao polyphenols are potent natural antioxidants with cardioprotective and anti-inflammatory action, which are susceptible to degradation, requiring technological approaches to guarantee their protection, stability, and controlled release. Here, 21 cocoa polyphenol-rich microencapsulates were produced by spray-drying and freeze-drying techniques using two wall materials (maltodextrin and gum arabic). Chemical (total and individual phenolic content and antioxidant activity), structural (morphology), and biological parameters (cytotoxicity, trypanocidal, antioxidant, and immunomodulatory activities) were assessed to determine the most efficient microencapsulation conditions on Trypanosoma cruzi-infected myocardioblast and macrophage cells. Significant antiproliferative properties against infected cells (superior to benznidazole) were found in two microencapsulates which also exhibited cardioprotective properties against oxidative stress, inflammation, and cell death.